Identification of Adult Mesodermal Progenitor Cells and Hierarchy in Atherosclerotic Vascular Calcification. (9th March 2018) - Cho, Hyun-Jai; Lee, Jin-Woo; Cho, Hyun-Ju; Lee, Choon-Soo; Kim, Hyo-Soo
Abstract : The nature of calcifying progenitor cells remains elusive. In this study, we investigated the developmental hierarchy and dynamics of progenitor cells. In vitro and in vivo reconstitution assays demonstrated that Sca-1+/PDGFRα– cells in the bone marrow (BM) are the ancestors of Sca-1+/PDGFRα+ cells. Cells of CD29 + Sca-1+/PDGFRα– lineage in the BM showed both hematopoietic potential with osteoclastic differentiation ability as well as mesenchymal stem cell-like properties with osteoblastic differentiation potential. Clonally-isolated BM-derived artery-infiltrated Sca-1+/PDGFRα– cells maintained osteoblastic/osteoclastic bipotency but lost hematopoietic activity. In hypercholesterolemic apolipoprotein-E-deficient (Apoe-/-) mice, the mobilization from BM to peripheral circulation, followed by migration into atherosclerotic plaques of Sca-1+/PDGFRα– cells, but not Sca-1+/PDGFRα+ cells, were significantly decreased, and Interleukin-1β (IL-1β) and Interleukin-5 (IL-5) mediated this response. Here, we demonstrated that Sca-1+/PDGFRα– cells are mesodermal progenitor cells in adults, and the dynamics of progenitor cells were regulated by atherosclerosis-related humoral factors. These results may contribute to better understanding of vascular homeostasis and assist in the development of novel therapies for atherosclerosis. Abstract : Mesodermal progenitor cells (MPCs), which exist in the adult bone marrow, are the common ancestors of hematopoietic and mesenchymal stem cells, and mobilize into peripheral blood and infiltrate the arteries. We demonstrated that Sca-1+/PDGFRα– cells are MPCs in adults, and that the progenitor cell dynamics were regulated by atherosclerosis-related humoral factors.